John Nicholson family papers - Nicholson, John, 1757-1800.
Correspondence, diary fragments (1796-1797), business and financial records, and printed matter. The papers relate primarily to the Pennsylvania Land Company, the Asylum Company, and to Nicholson's other land holdings in Pennsylvania, the western territories, and Washington, D.C. Papers of Nicholson's heirs relate to attempts by them to regain properties that had been alienated. Correspondents include Thomas Bedwell, James M. Broom, Thomas Joubert, Edward Livingston, Louis McLane, Robert Morris, and Roger Brooke Taney.
Financier and land speculator.
Collection material in English.
Keywords: Bedwell, Thomas -- Correspondence; Broom, James M. -- 1776-1850 -- Correspondence; Morris, Robert, -- 1734-1806 -- Correspondence; Joubert, Thomas -- Correspondence; Livingston, Edward, -- 1764-1836 -- Correspondence; McLane, Louis, -- 1786-1857 -- Correspondence; Taney, Roger Brooke, -- 1777-1864 -- Correspondence; Nichols family; Asylum Company; Pennsylvania Land Company; Land tenure -- Northwest, Old; Land tenure -- Pennsylvania; Land tenure -- Washington (D.C.); Land speculation -- Pennsylvania; Financiers; Land speculators